Acquiring through Letting Go the Bikkurim Commandment and the Foundations of Private Property - Lavi, Aharon Ariel (International Journal of Civilizations Studies & Tolerance Sciences, 2025)
The legitimacy of private property is a fundamental question in both economic theory and Jewish thought, as it seeks to resolve the paradox of how mortal beings can claim ownership over a world ultimately belonging to its eternal Creator. Jewish economic thought asserts that all private ownership derives from divine ownership and necessitates acknowledgment of this reality. This issue extends beyond theology, intersecting with modern political and economic discourse. This paper explores the similarities and differences between Jewish and Western philosophical perspectives on property by comparing John Locke’s theories of private ownership with Talmudic concepts found in Tractate Bikkurim of the Jerusalem Talmud. While both frameworks view creation as a divine blessing, Locke perceives it as an invitation for individuals to establish ownership through labor, promoting economic growth without intrinsic moral constraints. In contrast, the Talmud emphasizes a necessary transition between divine and human domains, advocating for limitations on ownership and wealth accumulation. It warns that unchecked human ambition endangers both individuals and society, upholding humility, restraint, and the relinquishment of absolute ownership as a moral imperative. By juxtaposing these perspectives, this study aims to enrich contemporary economic discourse and foster a deeper understanding of the ethical dimensions of property rights, as a venue to increase tolerance and understanding between religions, societies and civilizations.